2007
DOI: 10.1002/elps.200700070
|View full text |Cite
|
Sign up to set email alerts
|

Recent accomplishments in the field of enantiomer separation by CEC

Abstract: Recent accomplishments in the field of enantiomer separation by CECThe present review intends to summarize recent developments in the field of enantioselective separations and analysis by CEC. It covers studies published in English language in common peer-reviewed journals within the period between 2003 and 2006. Both, methods making use of chiral mobile phase additives as well as chiral stationary phases for electrochromatographic enantiomer separations, are reviewed. Achievements that have been made on the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
51
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 106 publications
(151 reference statements)
0
51
0
Order By: Relevance
“…Enantiomeric separations with CDs in capillaries coated with a polyelectrolyte multilayer has been reported [67,68] but in this case the CD used was neutral and therefore no coating of the capillary with the CD itself as in this study was observed. No further attempts were achieved in this study to optimize the thickness of the adsorbed CD layer which may enhance enantiorecognition [63].…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Enantiomeric separations with CDs in capillaries coated with a polyelectrolyte multilayer has been reported [67,68] but in this case the CD used was neutral and therefore no coating of the capillary with the CD itself as in this study was observed. No further attempts were achieved in this study to optimize the thickness of the adsorbed CD layer which may enhance enantiorecognition [63].…”
mentioning
confidence: 94%
“…Unfortunately, the stereoisomers were co-migrating in the absence of HS-g-CD in the BGE, their interaction with the HS-g-CD of the coating being not sufficiently enantioselective. This is probably due to the thin stationary phase film obtained resulting in a low sample capacity [63]. This result is however very interesting since it shows that this type of coating could dramatically alter the mobility and thus the separation of chiral or non-chiral analytes.…”
mentioning
confidence: 98%
“…In CEC, the chiral selectors are immobilized in packed, monolithic or open-tubular (OT) capillaries. [8][9][10][11] Besides, both the high efficiency of CE and the high selectivity of HPLC are coupled in CEC; the immobilization of the chiral selectors onto the packed, monolithic materials or the inner surface of the capillary can avoid the UV background, according to the selector. Preinerstorfer et al have reported the preparation of a monolithic silica capillary column modified with cinchona alkaloid derivatives to separate dipeptides in non-aqueous CEC.…”
Section: Introductionmentioning
confidence: 99%
“…The other option is the postmodification approach, in which a monolith with reactive groups, such as the epoxide groups of glycidyl methacrylate (GMA), is modified by reacting with various chromatographic ligands such as amino acid [6], chiral selector [7], N-ethylbutylamine [8], and affinity ligand [9]. There are considerable advantages for this approach [10,11]: firstly, the reactive monolith that allows a subsequent modification has to be optimized only once. In addition, the bonded ligands are fully exposed to the interface between the stationary phase and the mobile phase, which is favorable for chromatographic interactions.…”
Section: Introductionmentioning
confidence: 99%